Health Literacy by Telehealth Apps to Decrease Breast Cancer Diagnosed - Feranita Kumalasari; Nathania; Reny I'tishom (Universitas Airlangga, 2024)
Background: Health literacy always being one of the health promotion ways to support the SDGs program in creating the better life for people surroundings. Health literacy try to make accessible information for positive impact in stimulating people awareness about disease especially in malignant such as breast cancer. Breast cancer still being on the first place of cancer's rank with high number of affected people. The digitalization in health literacy offers the service like online consultation, suggested daily diet, suggested time duration to do physical activities based on personal data of the user, and others. Aims: This study was to evaluate the application of technology being used in health literacy to decrease the number of breast cancer diagnosed around the world. Methods: This literature review databases were searched using online journal from Google Scholar, PubMed, ScienceDirect, online article, and WHO newsletter. This study focuses on the development of telehealth using in health literacy for malignant. Results: The digitalization in health literacy for promoting SDGs program to reduce the number people affected by breast cancer help people surroundings accessing their health personal data and to remind the suggested schedule to do medical checkup for malignant and suggested daily lifestyles. So that the target to support SDGs health promotion way in people awareness about cancer can be reached effectively. Conclusion: Telehealth using in the digitalization of health literacy give positive impact in stimulating people awareness about breast cancer, which lead to the decreasing number of people affected by breast cancer around the world.